Administration of Iodine-125 Seeds Promotes Apoptosis in Cholangiocarcinoma through the PI3K/Akt Pathway - Junqing Lin; Leye Yan; Xiaolong Wang; Zhengzhong Wu; Kun Ke; Xin Lin; Ning Huang; Weizhu Yang (Advances in Polymer Technology)
Purpose. We aimed to examine the effects of 125I seeds on the gene expression of Bcl-2, Bax, and PI3K/Akt pathway components in cholangiocarcinoma cells. Methods. In vitro, human cholangiocarcinoma RBE cells were treated with 125I seeds (0.39 mCi or 0.85 mCi) for 72 h, 120 h, and 168 h. Cell proliferation and apoptosis were assessed. The expression of Bcl-2 and Bax was detected by RT-PCR, and Western blotting was carried out to explore changes in Akt activity. Result. 125I seeds inhibited the proliferation of RBE cells. The apoptosis rate of the RBE cells in the low-activity group was significantly higher than that in the high-activity group at 120 h and 168 h, while no difference was found between the two groups at 72 h. After 120 h of culture, the gene expression of Bcl-2 and Bax decreased in both groups, the ratio of Bcl−2/Bax in the low-activity group decreased, and the PI3K/Akt signaling pathway was inhibited in both groups. Conclusion. 125I seeds affect the proliferation and apoptosis of cholangiocarcinoma cells in a dose-dependent manner. The therapeutic effect of low-activity 125I seeds on cancer cells may be better. 125I seed brachytherapy may promote the apoptosis of cholangiocarcinoma cells by inhibiting the PI3K/Akt signaling pathway and regulating the Bcl−2/Bax ratio.